PENGUATAN KAPASITAS BUMG BERSAMA MINAPOLITAN MEURASA SABAN KABUPATEN ACEH TIMUR MELALUI EDUTEKNOPRENEURSHIP - Muhammad Baihaqi; Syardiansah Syardiansah; Zulkarnen Mora (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
Gampong-Owned Enterprises (BUMG) Minapolitan Meurasa Saban is a business entity owned by 5 villages (bale buya, matang gleum, kuala leuge, seuneubok peusangan and seuneubok pidie). with one of their business is BUMDES Mart Minapolitan Meurasa Saban. The weakness of administrative and financial as well as manual product registration are problems encountered in marketing the products on display at BUMG. The purpose of this program is to improve administrative and financial management staffs  based on edutechnopreneurship. The activity was carried out for 5 months starting from May to September 2019. The activities involved 15 BUMG management and supervisors of  Minapolitan Meurasa Saban. The method used is discussion and active participation of the target group by applying adult learning model. The activities were carried out in several stages which included coordination, socialization, training and mentoring activities. The results of the evaluation of the implementation of the activity showed that there was an increase in the capacity of BUMG's Bersama Minapolitan Meurasa Saban supervisors and management staffs on improving BUMG's administrative and financial governance. The results of the questionnaire showed that 10 administrators (75%) understood all the training material well, while 5 administrators (25%) understood all the training material. The level of satisfaction of the training participants showed 12 managers (85%) were very satisfied and 3 administrators (15%) were satisfied with the implementation of the training. BUMG Bersama Minapolitan Meurasa Saban supervisors and administrators have understood AD / ART and TUPOKSI, whereas the treasurer and operator of BUMG Bersama Minapolitan Meurasa Saban are able to understand the edutechnopreneurship-based product registration, BUMG Bersama Minapolitan Meurasa Saban has a business development plan as stated in the annual work programKey word:  BUMG Bersama Minapolitan Meurasa Saban, Aceh Timur District, Edutechnopreneurship